Food, sound, and social interaction: Investigating the cultural significance of music in culinary practices in javanese society - Sularso Sularso; Isti Syafitri Andini; Saifuddin M.F.; Ratna Ma’rifah Destri; Ratnawati Hermanto Sarwendah; Pratiwi Purbosari Purwanti (BIO Web of Conferences)
This study explores the cultural significance of music in culinary traditions, examining how sound fosters social interaction, strengthens community ties, and enhances the sensory experience of food. Despite the longstanding relationship between music and food in various cultures, research on its impact on social bonds and cultural identity is limited. The study utilizes semi-structured interviews with chefs, ethnomusicologists, and cultural practitioners, alongside participant observation at cultural festivals, communal meals, and rituals in Java. The findings reveal that music enhances the sensory perception of food and creates an atmosphere that strengthens communal bonds during meals. It also carries symbolic meanings linked to cultural rituals, serving as a way to transmit culinary knowledge and reinforce cultural identity. Specific soundscapes evoke emotional responses that complement the taste and texture of food, resulting in a more immersive dining experience. The study concludes that music is not just an accompaniment to food but an essential part of culinary traditions, promoting social cohesion and preserving cultural heritage. By highlighting the multisensory connection between sound and food, this research broadens our understanding of how music shapes communal dining experiences and cultural identities across societies. It also opens new interdisciplinary avenues between ethnomusicology, anthropology, and sensory science.